Metode Pendidikan Tradisional Pesantren dalam Membina Akhlak Santri (Studi Pesantren Nahdlatul Ulum Kabupaten Maros) - W, Wirayanti; E, Erna; C, Cherawati; S, Khaerani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to examine the traditional educational methods applied at Pesantren Nahdlatul Ulum, Maros Regency, in fostering the moral character of its students. As a traditional Islamic educational institution, pesantren plays a significant role in shaping the character and morals of the younger generation. Through a descriptive qualitative approach, this research analyzes various teaching methods, such as the sorogan method, bandongan, and direct mentorship by the kiai. The findings reveal that the pesantren's educational methods, which prioritize emotional closeness between teachers and students, strict spiritual discipline, and the intensive application of Islamic values, are effective in nurturing the moral integrity of the students. The personal bond between the kiai and students is a key factor in the internalization of ethical and spiritual values. These findings are expected to provide significant contributions to the development of moral education methods in other pesantren and serve as a reference for strengthening the role of pesantren as a center for character education in Indonesia.